Supervisi Model Akademik Terbukti Meningkatkan Kepatuhan Identifikasi Pasien Oleh Perawat - Agista Paramitha Sari; Regista Trigantara; Diana Noor Fatmawati (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Patient identification compliance is important in preventing patient safety incidents, so the role of the head of the room through supervision is needed to ensure that the implementation is in accordance with procedures. This study aims to determine the effect of academic model supervision in improving compliance with patient identification by nurses. The type of research is quantitative with One Group Pretest-Posttest Design. This study took the population of implementing nurses at the Inpatient Installation of Malang City Hospital as many as 55 respondents. Based on purposive sampling technique, a sample of 49 respondents was obtained. Data collection using observation sheets. The data were analyzed univariately and bivariately using the Wilcoxon test and obtained a p-value of 0.000 (<0.05). The results of this study show that the supervision of the academic model of the head of the room has a significant influence on improving the compliance of patient identification by nurses at the Inpatient Installation of Malang City Hospital. The head of the room is given the opportunity to attach a sense of responsibility and compliance of the implementing nurse to the standard procedures that have been set through the application of academic model supervision in educative, supportive, and managerial activities.